Small business taxes made easy : how to increase your deductions, reduce what you owe, boost your profits, and build a dynasty - Rosenberg, Eva (McGraw Hill Education on BrillianceAudio., 2017)
The go-to tax guide for small-business owners is packed with tips for dramatically lowering taxes. This third edition covers key provisions passed by Congress that will affect taxes for 2016 through 2020. This third editionn includes: Enhanced checklists; Improved entity comparisons; Updates on valuable business resources and tools; Information about depreciation; Critical home-office information; Need-to-know online business issues; Expanded tips on Tax Notices and audits; and more. Covering more thanb just taxes, this small business guide also includes business plans, legal taxcutting tips, and ways to build a dynasty, or develop a smart exit plan.